Opening up research data from the perspective of higher education - Piskorz-Ryń , Agnieszka (Prawo Kanoniczne, 2024)
The article addresses the issue of reusing research data as part of the right to public sector information in the context of the development of the ideas of open government and open science. The aim of the study is to analyze the legal regulations concerning the reuse of research data at the level of European Union law and Polish law. The study reconstructs the concept of ‘research data’ and discusses the principles of its disclosure, including the principle of ‘default openness’ and the FAIR standard. It also presents the conditions, scope and limitations of the re-use of research data, in particular with regard to public funding and the sharing of data through institutional and thematic repositories. The conclusion identifies the main challenges facing higher education institutions in implementing this issue.